Aplikasi Absensi Pegawai Kecamatan Batuceper Tangerang Dalam Meningkatkan Akurasi Informasi - Rachman Mulyandi; Cynthia Ayu Wulan Dini (Universitas Raharja, 2014)
Subdistrict Batuceper a government agency employee attendance system is still running it manually . Where the application of the attendance system there are some things that become obstacles . The problems that occur are in terms of effectiveness , efficiency and process time of roll call . Attendance report form which is currently still in the form of writing that can complicate the search process the data , and the possibility of missing attendance data . With the above reasons , the author tries to provide alternative solutions to the problem by creating an application that will record attendance system employee attendance , time of arrival , time of return , which will be made in a systematic and computerized . This system eliminates the process of recording employee attendance that still run manually , ie by reducing the error rate by means of input personal identification number in the attendance process . At this writing will also be explained stages of processing , ranging from processanalysis , planning, design using the programming language PHP ( Hypertext Prepocessor ) and MySQL database , until the implementation stage using spiral with engineering notation and object -oriented approach , UML ( Unified Modeling Languange ) , in order to determine what data is being input and output on the system running . With the attendance information system is expected to minimize the constraints that occur in the system before.